Analisa Sifat Mekanis Velg Aluminium Sepeda Motor Menggunakan Metode Heat Treatment Dengan Variasi Waktu Kelipatan 3 Jam Pada Suhu Aging 150ºC - Bambang Setiadi; Lanjut Martupa Dimmers Lumban Toruan (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
ABSTRACT Aluminum is a metal that has strong, lightweight, and corrosion-resistant properties, so it is widely used in household, automotive, and industrial applications, one of which is motorcycle wheels. In this study, motorcycle wheels made of aluminum material will be heat treated (quenched) at a temperature of 415oC with a waiting time of 1 hour and using a salt water solution cooling medium, then heat treatment (artificial aging) is carried out again at a temperature of 150oC with a waiting time of 3 hours. for 3 samples and cooled naturally, this study aims to study the effect of heat treatment on the hardness profile of motorcycle aluminum alloy wheels that are heat treated, and this study also conducted microstructure testing. The results of the initial surface hardness test were 82.38 HV, after (Quenching) 64.98HV and after Aging 3 hours 105.22 HV, Aging 6 hours 107.14 HV, Aging 9 hours 116.5 HV. Keywords: Aluminum, Rims, heat treatment, surface hardness